Strategi Pengembangan Agrowisata Kebon Gulo, Kecamatan Musuk, Kabupaten Boyolali - Rahmawati, Mainurlisma; Mariyono, Joko; Prayoga, Kadhung (Universitas Galuh, 2025)
Agritourism is an alternative to tourism that utilizes agricultural aspects as a tourist attraction. The agritourism object that is currently developing in Boyolali is Kebon Gulo Agrotourism, which is located in Musuk District, Boyolali Regency. Kebon Gulo Agritourism in its implementation has not shown optimal development. This is indicated by fluctuations in the number of visitor arrivals at Kebon Gulo Agrotourism. This research aims to identify internal factors and external factors of Kebon Gulo Agrotourism and formulate alternative strategies for the development of Kebon Gulo Agrotourism. This research was conducted in December 2024 - January 2025 at Kebon Gulo Agrotourism which is located in Musuk District, Boyolali Regency. The method used is a method with a case study approach, which is used to identify and control events that occur both from inside and outside Kebon Gulo Agrotourism based on field facts. The data used in this study are internal data (strengths and weaknesses) and external data (opportunities and threats) from Kebon Gulo Agrotourism. The data analysis method uses descriptive methods, IFAS, EFAS, SWOT and AHP analysis. The results showed that the position of Kebon Gulo Agrotourism was in quadrant I with a development strategy based on its priorities, among others; 1) a strategy to improve quality by improving the quality and development of human resources; 2) strategies to improve ancillary by creating message impression service boards and procuring socialization activities; 3) strategies to improve accessibility by developing websites and collaborating with schools; 4) strategies to improve amenities, namely adding photo spot facilities and souvenir centers; 5) strategies to increase attractions with attraction and agro-tourism innovation.